A case of renal angiomyolipoma treated with partial nephrectomy. Diagnostic value of ultrasonography and computed tomography - Ito, N (Hinyokika kiyo. Acta urologica Japonica, 1987)
A 62-year-old woman with renal angiomyolipoma is reported. Ultrasonogram revealed a hyperechoic renal mass and computed tomography showed a fatty density area in the tumor. Preoperative diagnosis of renal angiomyolipoma was made and was confirmed by frozen section during the operation. Partial nephrectomy was performed subsequently. Renal angiomyolipoma is known by its fat content causing high echogenicity in the ultrasonogram and fatty density area in computed tomography. Renal angiomyolipoma, therefore, could be suspected by this combination of findings and conservative surgery should be planned preoperatively